2012
DOI: 10.1063/1.3675489
|View full text |Cite
|
Sign up to set email alerts
|

Large enhancement of magnetostriction due to compaction hydrostatic pressure and magnetic annealing in CoFe2O4

Abstract: Polycrystalline CoFe2O4 was produced by a ceramic method. The heat-treated powder was pressed, varying the hydrostatic pressure between 87 and 278 MPa, and was heat-treated again at 1350 °C for 24 h. All magnetic parameters showed a clear dependence on this hydrostatic pressure. The saturation magnetization showed a minimum, and the coercivity, the anisotropy, and the magnetostriction showed a maximum at compaction pressures around 150 MPa. This pressure dependence of the magnetic parameters can be explained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 10 publications
5
37
0
Order By: Relevance
“…H app. [ 0.5 T), the magnetostriction goes up steadily to approach its [25]. The resulting increase is an indication of the increase in magnetocrystalline anisotropy, which agrees with the observed increase in coercive field in the prepared composites (see Table 1).…”
Section: Resultssupporting
confidence: 85%
“…H app. [ 0.5 T), the magnetostriction goes up steadily to approach its [25]. The resulting increase is an indication of the increase in magnetocrystalline anisotropy, which agrees with the observed increase in coercive field in the prepared composites (see Table 1).…”
Section: Resultssupporting
confidence: 85%
“…It has been experimentally shown that magnetostrictive properties of materials derived from cobalt ferrite, including the strain derivatives, are dependent on processing conditions. [25][26][27] In another study, 28 it was suggested that an enhancement of $200% in strain sensitivity may be due to non-stoichiometry which can also be related to the processing conditions. Therefore it is important to discuss the effect of Zn-substitution on the strain derivative of the samples with respect to the unsubstituted sample in the present study (i.e., x ¼ 0).…”
Section: Magnetostrictive Propertiesmentioning
confidence: 99%
“…This can be done by magnetic annealing [11][12][13][14][15], magnetic-field-assisted compaction [16,17], or reaction under uniaxial pressure [18]. Another way to tune magnetostrictive properties of CoFe 2 O 4 is by substitution of the Fe atoms by Mg, Al, Ti, Mn, Ni, Cu, Zn, Ga, Zr, Nb, In, etc., or even rare-earth elements [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%